Porphyrin-Based Metal-Organic Frameworks for PD-L1 Detection via "Coordination Disaggregation-Induced Enhancement" Strategy - Gong, Weiming (Langmuir : the ACS journal of surfaces and colloids, 2025)
Porphyrins, known for their exceptional photoelectrochemical properties and high luminescence, are promising candidates for electrochemiluminescence (ECL) applications. However, their tendency to aggregate in aqueous solutions due to π-π stacking leads to luminescence quenching and reduced efficiency. To address this, we developed a "coordination disaggregation-induced enhancement" strategy, utilizing metal-organic frameworks (MOFs) as stable platforms for immobilizing porphyrin. These porphyrin-based MOFs not only increase the loading of luminescent groups and suppress the aggregation-caused quenching (ACQ) effect but also enhance electron transfer via uniform dispersion of pyrrole N in the porphyrin ligand, thereby improving ECL intensity. Additionally, they exhibit favorable biocompatibility and low toxicity, making them suitable for biomedical applications. By combining porphyrin-based MOFs as donors with PDAMnO2 composites as quenchers, we constructed a quenching-type ECL immunosensor for detecting programmed death ligand 1 (PD-L1). This sensor achieves a detection range of 10 fg/mL to 100 ng/mL, with a limit of detection as low as 2.48 fg/mL, which demonstrates great potential for highly sensitive biomarker detection and promising applications in early cancer diagnosis and other medical diagnostics